Slavic languages as object of scientific research: structure and functioning - Kazlouskaja, Liudmila A. (Journal of the Belarusian State University. Philology, 2021)
The purpose of this article is to present specific research results associated with systematic description of the functional and structural features of the Slavic languages made by the theoretical and Slavic linguistics department of the faculty of philology, Belarusian State University. The presented studies focus on the use of significantly expanded methodological apparatus (pragmatic, corpus linguistic, discourse analysis etc.) to the study of Slavic languages. The comparative study of Slavic languages made it possible to identify important patterns of their functioning, which is essential to humanities in general and Slavic studies in particular, including teaching Slavic and non-Slavic languages. The research results are applicable to teaching Slavic languages in higher education, improving programs for teaching native and foreign languages in secondary educational institutions; applied areas such as automated translation, language training programs, parallel and monolingual text corpora etc., further development of comparative and theoretical linguistic research, language modelling, improvement of public discourse including mass media language and metalanguage of educational literature.
Keywords: Slavic philology; Slavic languages; linguoculturological space; language situation